Pulmonary Azygous Lobe-An Anatomical Variant - Seiber, W; Karcara, N; Pant, P (Kathmandu University Medical Journal, 2015)
Pulmonary azygous lobe is one of the common lung malformations. There is only few article about azygous lobe. Its a small accessory lobe sometimes found on the upper part of the right lung, separated from the rest of the upper lobe by a deep groove lodging the ayzygous vein. This reports describes the presence of azygous lobe, a rare anatomical variant, encountered during chest x-ray discussion. We describe here the anatomical basis and the clinical significance of azygous lobe. Kathmandu University Medical Journal Vol.12(2) 2014: 151-152